INKONSISTENSI LOGIKA DALAM PERKARA TINDAK PIDANA KORUPSI - Widiada Gunakaya (Jurnal Yudisial, 2011)
ABSTRACTThe court decision as final phase of enforcement and application of law, as a normative it is properly to reflect material truth, justice values, utility and it has legal certainty will as. In connection with the decision court of BMS No.44/Pid.B/2008/PN.Bms, the accused has been stated proved guilty committed "the criminal act of corruption as a continuous" with the State suffered losses as much as 117.535.350 IDR. According the verdict, The court decision has been applicated the provisions of Article 197 Paragraph (1) regarding Law of criminal procedure in general. Yet in connection with substantive criminal law, the court was not applicate as a truth the elements of unlawfulness (actus reus) and criminal liability (men rea) as conditional sentence. Legal reasoning likewise, was not excute as a systematical and logical yet, including the values of justice was not fulfil appreciate in the court decision anyway.Keywords : criminal act, criminal liability, material unlawfulness, certain of law, and justice ABSTRAKPutusan pengadilan merupakan akhir dari penegakan dan penerapan hukum yang secara normatif mengandung kebenaran materiil, kejujuran, nilai keadilan, manfaat dan kepastian hukum. Dalam keterkaitan dengan putusan pengadilan No.44/Pid.B/2008/PN.Bms, menyatakan terdakwa bersalah melanggar ketentuan korupsi dimana negera dirugikan sebesar Rp. 117.535.350,-. Merujuk pada putusan tersebut, secara umum putusan pengadilan mengaplikasikan pasal 197 Paragraph (1) dalam hukum acara pidana. Meski sudah terkait dengan hukum pidana substantif, pengadilan belum mengaplikasikan unsur-unsur unlawfulness atau actus reus, dan pertanggungjawaban pidana sebagai pertimbangan hukuman. Dasar hukum yang digunakan belum mengendepankan logika dan sistematis, termasuk nilai-nilai keadilan dalam putusan pengadilan. Kata kunci: hukum kejahatan, pertanggungjawaban pidana, bukti yang tidak syah, kepastian hukum, keadilan